1957
DOI: 10.1152/ajplegacy.1957.189.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Reflexes in Pulmonary Edema?

Abstract: The mechanism of pulmonary edema caused by stimulation of the central nervous system was studied in 33 dogs. Stimulation was obtained by the intracisternal injection of veratrine, or of air or saline under high pressure, or by electric stimulation of the hypothalamus. Pressure changes in the pulmonary artery, left atrium and left ventricle were recorded by means of three catheters introduced through the right external jugular vein and the left femoral artery. Experiments were performed with closed or open ches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1959
1959
1970
1970

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Contrary to our previous experience in open chest experiments (8) and in agreement with studies of Wiggers (9,10), who proved that either increased venous return or increased peripheral resis tance is followed by increase in ventricular diastolic pressure in heart-lung preparations, it was actually noted that left ventricular diastolic pressure rose in most experiments. However, this rise usually started 20 or more m inutes alter the rise of systolic pres sure, indicating that other mechanisms were able to m aintain an increased left ventricular work for a relatively long time without requiring m arked dilatation.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Contrary to our previous experience in open chest experiments (8) and in agreement with studies of Wiggers (9,10), who proved that either increased venous return or increased peripheral resis tance is followed by increase in ventricular diastolic pressure in heart-lung preparations, it was actually noted that left ventricular diastolic pressure rose in most experiments. However, this rise usually started 20 or more m inutes alter the rise of systolic pres sure, indicating that other mechanisms were able to m aintain an increased left ventricular work for a relatively long time without requiring m arked dilatation.…”
Section: Discussionsupporting
confidence: 85%
“…(2) suggested that central stim ulation was fol lowed by neurogenic systemic vascular constriction and pulmonic dilatation. T hat the latter phenomenon may occur was dem onstrat ed in this laboratory (8).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Other investigators have found a similar elevation of systemic blood pressure and pulmonary venous pressure after elevating intracranial pressure with bags, balloons (5, 6, 10, 11), and mineral oil (12). Similar hemodynamic changes can be produced by the intracisternal injection of veratrine (13,14), kaolin (15), a thrombin-fibrinogen mixture (16)(17)(18), and the injection of aconitine in the preoptic areas (19). The mechanisms that have been suggested for these hemodynamic changes accompanying elevated intracranial pressure or intracisternal injections include: ischemia (1,20), release of a pressor material (21), venocontriction (22,23), a myocardial intoropic response (22), and somatic and splanchnic shunting (24).…”
Section: Discussionmentioning
confidence: 63%
“…Visscher et al (341) have reviewed the physiological and pharmacological aspects of pulmonary edema, while Luisada and co-workers (342,343) have shown that the pulmonary edema resulting from powerful stimulation of the vasomotor center of the central nervous system is probably caused by excessive shift of blood from the systemic to the pulmonary circulation. Hawthorne et al (344) have shown that acute pulmonary edema can be produced by simultaneous creation of aortic insu fficiency and renal artery constriction, but that this type of pulmonary edema can be prevented by prior construction of an atrial septal defect (345).…”
Section: Abnormalities Of the Peripheral Circulationmentioning
confidence: 99%